Progress of all-perovskite tandem solar cells: the role of narrow-bandgap absorbers - Luo, Xinhui; Wu, Tianhao; Wang, Yanbo; Lin, Xuesong; Su, Hongzhen; Han, Qifeng; Han, Liyuan (Science China. Chemistry, 2021)
Perovskite solar cells (PSCs) have gained increasing attention due to their excellent photovoltaic performance, achieving certified power conversion efficiency (PCE) of 25.2%. To further enhance PCE and break the Shockley-Queisser limit of the single junction PSCs, great efforts have been made in tandem solar cells based on perovskite, including perovskite/Si, and perovskite/perovskite (all-perovskite). Among them, all-perovskite tandem solar cells exhibit unique advantages of both low-cost fabrication and high efficiency. They have advanced rapidly in these years, due to the realization of stable and efficient narrow-bandgap perovskites. In this work, we review the development of monolithic all-perovskite tandem solar cells and highlight the critical role of narrow-bandgap perovskites in recent progress of all-perovskite solar cells. We also propose our perspective of future directions on this subject.